2003
DOI: 10.1023/a:1024443112717
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The spike (S) gene of the porcine epidemic diarrhea virus (PEDV) Chinju99 which was previously isolated in Chinju, Korea was cloned and sequenced to aid in the development of genetically engineered vaccines and diagnostic reagents against PEDV. The nucleotide sequence encoding the entire S gene open reading frame (ORF) of Chinju99 was 4,152 bases long encoding 1,383 amino acids. It consisted of 1,001 adenine (24.1%), 849 cytosine (20.4%), 877 guanine (21.1%) and 1425 thymine (34.3%) residues. The Chinju99 S OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Spatiotemporal reconstruction of PEDV strains showed that South Korean Chinju99, isolated in 1999 (55), is the oldest PEDV pandemic group strain in Asia. The original strains of the pandemic group detected in Japan, Thailand, and China are all homologous with Chinju99, and their genomes have remained relatively stable (51), which implies that the pandemic group strains in Asian countries originated from South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Spatiotemporal reconstruction of PEDV strains showed that South Korean Chinju99, isolated in 1999 (55), is the oldest PEDV pandemic group strain in Asia. The original strains of the pandemic group detected in Japan, Thailand, and China are all homologous with Chinju99, and their genomes have remained relatively stable (51), which implies that the pandemic group strains in Asian countries originated from South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Although PEDV is known to have only one serotype at present, the genome of PEDV is widely to show genetic diversity, according to the analysis results using molecular biological methods [21][22][23]. The M protein genes of four Chinese strains (LJB/03, JS-2004-2, LZC, and QH) have been sequenced and reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although PEDV is known to have only one serotype at present, genome of PEDV is widely known to show genetic diversity, according to analysis results using molecular biological methods [3,[28][29][30]. Based on sequence analyses of M glycoprotein gene and N phosphoprotein gene, Korean PEDV isolates are different from foreign PEDV strains.…”
Section: Discussionmentioning
confidence: 99%